2008
DOI: 10.1111/j.1551-2916.2008.02330.x
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Reactivity Assessment of Light Burnt Magnesium Oxide

Abstract: Light Burnt magnesium oxide (MgO), also known as magnesia, has a variety of industrial applications, including as the basic ingredient of magnesium oxychloride (MOC) cement. However, it is found that the quality, reactivity in particular, of Light Burnt MgO could vary so much that the workability and performance of magnesia-based final products can be significantly affected. Consequently, how to measure the reactivity of MgO would be the key for the further development and success of industrial applications of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…The powder mineralogical compositions were determined by X-ray diffractometry (XRD, PANalytical X'pert) using Cu-Kα radiation (1.541874 Å, 40 mA, 40 kV) as the source, and with a scanning step of 0.05°. In addition, the reactivity of the magnesia powders was evaluated by using an accelerated reactivity method, as documented in the literature [21]. In this test, 5.0 g of the magnesia powder was mixed and stirred in 100 mL of acetic solution that had a concentration of 1.0 mol/L.…”
Section: Testing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The powder mineralogical compositions were determined by X-ray diffractometry (XRD, PANalytical X'pert) using Cu-Kα radiation (1.541874 Å, 40 mA, 40 kV) as the source, and with a scanning step of 0.05°. In addition, the reactivity of the magnesia powders was evaluated by using an accelerated reactivity method, as documented in the literature [21]. In this test, 5.0 g of the magnesia powder was mixed and stirred in 100 mL of acetic solution that had a concentration of 1.0 mol/L.…”
Section: Testing Methodsmentioning
confidence: 99%
“…Property information of the light-burnt and dead-burnt magnesia powders: (a): XRD diffractograms; (b): magnesia reactivity tested by the acetic-acid method[21]. Temperature evolutions of the MKPC pastes during setting.…”
mentioning
confidence: 99%
“…As peaks at smaller diffraction angles are desirable, the major characteristic peak of magnesia at 42 . 938 (2Ł) is used in the calculation (Chau and Li, 2008).…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…15 It measured the time needed for neutralisation to take place between magnesia powder and acetic acid solution. After many trials, it was found that reacting 5 g magnesia powder with 100 ml of 0 .…”
Section: Reactivity Of the Magnesiamentioning
confidence: 99%